2004
DOI: 10.1177/107424840400900106
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiologic Properties and Antiarrhythmic Actions of a Novel Antianginal Agent

Abstract: Ranolazine is a novel antianginal agent capable of producing anti-ischemic effects at plasma concentrations of 2 to 6 microM without a significant reduction of heart rate or blood pressure. This review summarizes the electrophysiologic properties of ranolazine. Ranolazine significantly blocks I(Kr) (IC(50) = 12 microM), late I(Na), late I(Ca), peak I(Ca), I(Na-Ca) (IC(50) = 5.9, 50, 296, and 91 microM, respectively) and I(Ks) (17% at 30 microM), but causes little or no inhibition of I(to) or I(K1). In left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
1
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
3

Relationship

1
9

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 114 publications
4
108
1
3
Order By: Relevance
“…8 Other potassium (I Ks , I to , I K1 ) and calcium (peak I Ca ), as well as Na/Ca exchanger, currents are not affected by ranolazine or are only reduced at much higher concentrations that are beyond the therapeutic range of the drug (2-10 µmol/L). 8 Previous studies have also shown that ranolazine blocks I Na with IC 50 of 294 µmol/L in canine ventricular myocytes (at 0.1 Hz) 20 and reduces V max with an IC 50 of > 100 µmol/L in Purkinje fibers and M cell preparations paced at a BCL of 500 ms. 8,9 In marked contrast to the lack of an effect of ranolazine at therapeutic concentrations on peak I Na in ventricular myocardium and Purkinje fibers, the drug has recently been shown to exert potent use-dependent block of peak I Na (estimated from depression of V max ) in canine atrial tissues. The atrial selective-effects of ranolazine to depress peak I Na and associated parameters, such as impulse conduction velocity, excitability, and post-repolarization refractoriness 21-23 , were shown to result from a more negative steady-state inactivation relationship for I Na in atrial than ventricular cells.…”
Section: Ionic Mechanismsmentioning
confidence: 99%
“…8 Other potassium (I Ks , I to , I K1 ) and calcium (peak I Ca ), as well as Na/Ca exchanger, currents are not affected by ranolazine or are only reduced at much higher concentrations that are beyond the therapeutic range of the drug (2-10 µmol/L). 8 Previous studies have also shown that ranolazine blocks I Na with IC 50 of 294 µmol/L in canine ventricular myocytes (at 0.1 Hz) 20 and reduces V max with an IC 50 of > 100 µmol/L in Purkinje fibers and M cell preparations paced at a BCL of 500 ms. 8,9 In marked contrast to the lack of an effect of ranolazine at therapeutic concentrations on peak I Na in ventricular myocardium and Purkinje fibers, the drug has recently been shown to exert potent use-dependent block of peak I Na (estimated from depression of V max ) in canine atrial tissues. The atrial selective-effects of ranolazine to depress peak I Na and associated parameters, such as impulse conduction velocity, excitability, and post-repolarization refractoriness 21-23 , were shown to result from a more negative steady-state inactivation relationship for I Na in atrial than ventricular cells.…”
Section: Ionic Mechanismsmentioning
confidence: 99%
“…Ranolazine, an antiangina agent, has been recently shown to inhibit persistent Na ϩ currents associated with cardiac ischemia and to suppress early afterdepolarization (EAD)-triggered arrhythmias in an experimental model of LQT3 by blocking the persistent Na ϩ current (2,52). Ranolazine has recently been successfully used to treat LQTS patients harboring Na v 1.5 ⌬KPQ mutations (14,34).…”
mentioning
confidence: 99%
“…In addition, little information is available about the inhibition of RAN (< 10 mΜ) on hypoxia-increased reverse I NCX before this investigation. Although RAN has been reported to inhibit reverse I NCX at high concentration (100 mΜ), whether it directly attenuates the hypoxia-enhanced reverse I NCX or not at therapeutically relevant concentrations (< 10 mΜ) in ventricular myocytes remains to be determined conclusively (29,30). In this study, I Na.L and I NCX were recorded simultaneously and alternately at an interval of 5 s in the same cell during hypoxia, and then the myocytes were treated with RAN (< 10 mΜ) or TTX (2 mΜ) to observe their effects on the two aforementioned currents.…”
Section: Discussionmentioning
confidence: 87%